The Effect of Using Cooking Oil as a Lubricant on Engine Temperature and Power Generated with Variations in Surfactant Addition - Hangga Wicaksono; Muhammad Arif Nur Huda; Alfianto Alfianto (Evrimata: Journal of Mechanical Engineering, 2025)
Lubricating oil was type of fluid needed by a machine to work. Significant changes in the temperature of the lubricating oil viscosity up to low level made the engine components less lubricated. It caused the engine components to heat up quickly due to the friction between the metals that became greater. Poor quality lubricant could cause deposits to appear in the engine room which resulted in the engine working harder. The purpose of this study was to investigate the effect of the use of cooking oil added with surfactants of estolides and diglycerides with percentages (2.5%, 5%, and 7.5%) as engine lubricants on engine temperature and power produced by motor vehicles. The research method used was an experiment on a 125cc gasoline motorcycle lubricant with standard conditions. The data taken in this study included engine temperature and power. The results showed that with cooking oil mixed with 7.5% estolides surfactants after heating produced power with an average value of 6.52 HP and a mixture of 5% diglyceride surfactant producing an average value of 5.87 HP, which had a higher average value compared to oil rated at 5.37 HP. When using 2.5% estolides, the lowest value was 83.67°C and using a diglyceride percentage of 7.5% produced the highest value, namely 107.03°C. The use of cooking oil had an influence on engine temperature and power. The average power value of 5.71 HP was higher than oil with a value of 5.37 HP. The engine temperature value using cooking oil was 92.7°C lower than oil with a value of 96.63°C